The Costs of Babylon – Linguistic Distance in Applied Economics - Ingo E. Isphording; Sebastian Otten (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
Linguistic distance, i.e. the dissimilarity between languages, is an important factor influencing international economic transactions such as migration or international trade flows by imposing hurdles for second language acquisition and increasing transaction costs. To measure these costs, we suggest to use a new measure of linguistic distance. The Levenshtein distance is an easily computed and transparent approach of including linguistic distance into econometric applications. We show its merits in two different applications. First, the effect of linguistic distance in the language acquisition of immigrants is analyzed using data from the 2000 U.S. Census, the German Socio-Economic Panel, and the National Immigrant Survey of Spain. Across countries, linguistic distance is negatively correlated with reported language skills of immigrants. Second, applying a gravity model to data on international trade flows covering 178 countries and 52 years, it is shown that linguistic distance has a strong negative influence on bilateral trade volumes. – – Die linguistische Distanz zwischen Sprachen, d.h. die Unterschiede in der Aussprache, der grammatikalischen Struktur, dem Wortschatz etc., beeinflusst als ein bedeutender Faktor internationale ökonomische Transaktionen wie den internationalen Handel oder internationale Migrationsströme. Eine höhere linguistische Distanz bedeutet höhere Transaktionskosten und höhere Kosten in der Spracherlangung. Um eine Messung der Kosten von Sprachbarrieren zu ermöglichen, nutzen wir in dieser Studie eine neue Methode der Erfassung sprachlicher Unterschiede. Die sogenannte Levenshtein-Distanz ist ein einfacher und transparenter Ansatz der linguistischen Forschung, der es ermöglicht, linguistische Distanz im Rahmen ökonometrischer Anwendungen zu instrumentalisieren. Die Vorteile dieses Ansatzes werden in zwei verschiedenen Anwendungen dargestellt. Zunächst zeigen wir den negativen Effekt einer ansteigenden linguistischen Distanz auf den Spracherwerb von Immigranten in Spanien, den USA und Deutschland. Die Ergebnisse sind konsistent über die Mikrodatensätze der verschiedenen Gastländer. Zweitens zeigen wir in einem Gravitätsmodell bilateraler Handelsströme die erheblichen negativen Auswirkungen sprachlicher Barrieren auf das Handelsvolumen in internationalen Handelsbeziehungen.
Keywords: J24; J61; F22; F16; 330; Linguistic distance; immigrants; language; transferability; human capital; international trade